In silico molecular docking investigation of Morus L. bioactive compounds as potential SIRT1 activators for endothelial anti-aging therapy - Rahma, Oktivani Adelathifa; Rohman, Mohammad Saifur; Akbar, Naufal Zulfikar; Rohman, Ibrahim Abdur; Nurwidyaningtyas, Wiwit (Universitas Brawijaya, 2026)
Background: The silent progression of vascular aging, characterized by endothelial dysfunction, has been closely linked to a decline in SIRT1 activity. Natural polyphenols have drawn increasing attention as potential modulators of this longevity-associated enzyme, offering therapeutic promise through antioxidant and anti-inflammatory effects. Objective: This study aimed to conduct an in silico analysis of natural SIRT1 activators, compare their interactions with simvastatin, and explore their structure-activity relationships to identify potential candidates for vascular-protective nutraceuticals or therapeutic adjuvants. Methods: Molecular docking was performed using PyRx 8.0 to assess ligand-SIRT1 interactions. Pharmacokinetic properties were evaluated through Lipinski’s Rule of Five and Veber’s Rule using SwissADME, while toxicity predicted with ProTox-II. Ligand-receptor interactions were visualized using LigPlot+. Result: Moracin demonstrated the strongest binding affinity to SIRT1 (–11.3 kcal/mol), followed by resveratrol (–9.6 kcal/mol), chlorogenic acid (–9.5 kcal/mol), and quercetin (–8.9 kcal/mol), all outperforming simvastatin (–8.4 kcal/mol). Moracin, resveratrol, and quercetin satisfied key drug-likeness criteria, while chlorogenic acid showed limitations in permeability. Toxicity profiling positioned resveratrol as the safest compound (GHS class 6), with moracin and quercetin also showing favorable profiles. Simvastatin exhibited broader toxicity risks. Conclusion: In silico and molecular docking results presented evidence for the potential of Morus L. polyphenols, especially moracin and resveratrol, as SIRT1 activators for endothelial anti-aging therapy. However, these findings remain predictive and require further validation through in vitro and in vivo studies to confirm the therapeutic efficacy and safety of these compounds as anti-aging agents.